Investigation of the stereodynamics of molecules and catalyzed reactions by CE - Trapp, Oliver (Electrophoresis, 2010)
The investigation of the molecular dynamics of stereoisomers and the study of the kinetics of reactions, in particular of catalyzed reactions, is of fundamental interest in chemistry, biochemistry, and medicine. Understanding how to control the transition state of a reaction allows for a directed design of new catalysts and benign processes. The integration of reactions and capillary or microchip-based electrophoretic separations is highly attractive to perform on-column derivatizations or enzymatic on-column digests of peptides and proteins for further characterization. The present review article focuses on the recent advances to study the stereodynamics of molecules and reaction kinetics of catalyzed processes by means of CE. Models and algorithms to evaluate interconversion profiles obtained by electrophoretic separation techniques are discussed with respect to the challenging demands of high separation efficiencies typical for electrophoretic techniques. Models used for evaluation are based on iterative computer simulation algorithms using the theoretical plate model or stochastic model of chromatography, empirical calculation methods, derived from equations used in chemical engineering, namely Damköhler analysis, and direct access with the approximation function and more recently with the unified equation, which can be applied to all kinds of first-order reactions taking place during a chromatographic or a electrophoretic separation. Furthermore, areas of applications are presented and discussed to give a guideline for using dynamic CE and on-column reaction electrophoresis to study kinetics of reactions and dynamic processes.